USING ENGLISH LOANWORDS IN IRAQI ARABIC WITH REFERENCE TO MEDICAL FIELD JARGON - Fatimah Jamal SaadAllah Al-Quraishi; Mohammad Salman Mansour (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Listening to medical staff conversations in Iraq makes any linguists overhear to examine the distinguished linguistic construction of different words and sentences combination. It is not so hard for English language researcher to discover, after five minutes later of the conversation, that most of the words in these conversations are basically English words, but in their Iraqi Arabic style. Loaning or borrowing words from one language into another one without translation, but with some morphological or phonological changes are very common phenomenon in language studies. In this paper, the researchers try to shed the light on the medical filed jargon that basically based on loaning and borrowing words from English language to Iraqi Arabic language. For that purpose, the researchers make some physically presence in hospitals, pharmacies, and medical complex to insure by their ears the exists of loaning words in medical staff conversations. A questionnaire has been built after that to collect data. The data reveal that the loanwords in medical field are really modified by the medical staff speakers to match the Iraqi Arabic language. The data also reveal that most of these modifications occur in number, gender, possession, the definite articles, negation, and word formation as morphological modification. While the phonological modifications occur in simple aspects of pronunciation. The paper suggests further areas that recently enriched with loanwords in Arabic language as a result of globalization and culture interaction.